Pengaruh Kualitas Produk, Persepsi Harga, Dan Lokasi Terhadap Keputusan Pembelian Di Journey Coffee - windy widya; Hairani Tarigan (Panorama Nusantara, 2022)
The reason of this study changed into to determine the effect of quality product, price persception, and location on purchase decision at journey coffee. This studies became performed primarily based on a survey. The population on this study had been all guests of journey coffee. The sample used in this study turned into 100 respondents. Sampling method using accidental sampling. The information collection technique used is a questionnaire that has been tasted for validity and reliability. The analytical method used in this observe is quantitative method. even as the information processing on this study is the Partial Least square (PLS) method the use of the smart PLS version 3.0 software. Based on the end result of the evaluation, it can be said that between quality product and purchase decision has positive and significant influence. There's a positive and significant of the price perception waviable on purchase decision.There's a positive and significant of location on purchase decision. For that reason, the variable of quality product, price perception and location have a positive and significant impact on purchase decision.